Kebijakan Penyelenggaraan Sekolah Rakyat menurut Peraturan Presiden No.120 Tahun 2025 Tentang Penyelenggaraan Sekolah Rakyat Perspektif Siyāsah Dustūriyyah - Amira, Dea Ananda; Khalid (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
Educational inequality remains a significant challenge, particularly for children from poor and extremely poor families. To address this issue, the government enacted Presidential Regulation Number 120 of 2025 concerning the Implementation of People's Schools (Sekolah Rakyat) as an affirmative educational policy aimed at expanding access to education for disadvantaged groups. This study aims to analyze the People's School policy and examine its conformity with the principles of Siyāsah Dustūriyyah. This research employs a normative legal research method using statutory, conceptual, and analytical approaches. The data sources consist of primary legal materials, including laws and regulations, the Qur'an, Hadith, and classical Islamic political jurisprudence literature, as well as secondary legal materials from books and scientific journals. The results indicate that the People's School policy reflects the principles of justice (al-‘adālah), public welfare (al-maṣlaḥah al-‘āmmah), trustworthiness (amanah), and governmental responsibility (ulil amri) within the framework of Siyāsah Dustūriyyah. Furthermore, the policy is consistent with the objectives of maqāṣid al-syarī‘ah, particularly the protection of intellect (ḥifẓ al-‘aql), life (ḥifẓ al-nafs), and wealth (ḥifẓ al-māl). Therefore, the People's School policy can be regarded as a strategic effort by the government to promote educational equity and social welfare, although its implementation requires sustainable funding, effective governance, and continuous evaluation.